Hydathodes in ferns: their phylogenetic distribution, structure and function. (13th June 2022) - Mehltreter, Klaus; Wachter, Hanna; Trabi, Christophe; Testo, Weston; Sundue, Michael; Jansen, Steven
Abstract: Background and Aims: Ferns are the second largest group of vascular plants and are distributed nearly worldwide. Although ferns have been integrated into some comparative ecological studies focusing on hydathodes, there is a considerable gap in our understanding of the functional anatomy of these secretory tissues that are found on the vein endings of many fern leaves. In this study, we aimed to investigate the phylogenetic distribution, structure and function of fern hydathodes. Methods: We performed a global review on fern hydathodes and their phylogenetic distribution, carried out an ancestral character state reconstruction, and studied the structure, guttation and elemental composition of salt residues of eight species, and the diurnal patterns of xylem pressure of two species. Key Results: Hydathodes are known from 1189 fern species, 92 genera and 19 families of 2 orders, Equisetales and Polypodiales. Stochastic character mapping indicated multiple gains and losses of hydathodes at the genus level, occurring especially during the last 50 million years of fern evolution. Hydathodes were located on the adaxial leaf surface and characterized by a cytoplasm-rich, pore-free epidermis, and became functional for several weeks after nearly complete leaf expansion. In two species, positive xylem pressure built up at night, potentially facilitating guttation. Guttation fluid was rich in Ca and often Si, but also contained P, Mg, Na and Al. Conclusions: Stochastic character mapping and the structural and functional diversity of hydathodes indicate multiple origins, and their presence/absence in closely related taxa implies secondary losses during fern evolution. Positive xylem pressure and high air humidity play an important role as drivers of guttation. Hydathodes may contribute to the regulation of leaf nutrient stoichiometry by the release of excessive compounds and minerals other than waste products, but the presence of essential chemical elements in salt residues also indicates possible leakage.